Variation in production of cyanogenic glucosides during early plant development: A comparison of wild and domesticated sorghum - Cowan, Max F.; Blomstedt, Cecilia K.; Møller, Birger Lindberg; Henry, Robert J.; Gleadow, Roslyn M. (Phytochemistry (Oxford), 2021)
Domestication has narrowed the genetic diversity found in crop wild relatives, potentially reducing plasticity to cope with a changing climate. The tissues of domesticated sorghum (Sorghum bicolor), especially in younger plants, are cyanogenic and potentially toxic. Species of wild sorghum produce lower levels of the cyanogenic glucoside (CNglc) dhurrin than S. bicolor at maturity, but it is not known if this is also the case during germination and early growth. CNglcs play multiple roles in primary and specialised metabolism in domesticated sorghum and other crop plants. In this study, the temporal and spatial distribution of dhurrin in wild and domesticated sorghum at different growth stages was monitored in leaf, sheath and root tissues up to 35 days post germination using S. bicolor and the wild species S. brachypodum and S. macrospermum as the experimental systems. Growth parameters were also measured and allocation of plant total nitrogen (N%) to both dhurrin and nitrate (NO3−) was calculated. Negligible amounts of dhurrin were produced in the leaves of the two wild species compared to S. bicolor. The morphology of the two wild sorghums also differed from S. bicolor, with the greatest differences observed for the more distantly related S. brachypodum. S. bicolor had the highest leaf N% whilst the wild species had significantly higher root N%. Allocation of nitrogen to dhurrin in aboveground tissue was significantly higher in S. bicolor compared to the wild species but did not differ in the roots across the three species. The differences in plant morphology, dhurrin content and re-mobilisation, and nitrate/nitrogen allocation suggest that domestication has affected the functional roles of dhurrin in sorghum. [Display omitted] •All Sorghum species contain the cyanogenic glucoside dhurrin and can be toxic.•Morphological and biochemical changes were mapped over time in wild and cultivated species.•Contrary to expectations, concentrations were much lower in the wild relatives.•Dhurrin is unlikely to be effective in herbivore defence in the wild relatives.•The function of dhurrin appears to be different in wild and domesticated species.